Internationale Cash Flow-Rechnungen aus Eigner- und Gläubigersicht - Gernot M. Becker; Norbert Seeger (Hochschule für Bankwirtschaft (HfB), 2003)
Cash flow statements have gained popularity worldwide and are now mandatory also under German GAAP for listed companies. Based on International Accounting Standard No. 7 we review their analytical value from both a shareholder's and a creditor's point of view. Cash flow patterns do vary from earnings patterns. Income earned is not identical with cash received. Enron and some other spectacular insolvency cases are just examples of this. In the first part of this working paper we present the concept of the cash flow statement and discuss cash flow patterns of firms, cash flow ratios and their usefulness, but also the limitations the analyst should be aware of. In the second part we analyse the relevance of cash flow statements for banking institutions. Banks also have to present them in their annual accounts, but interestingly both investment and credit analysts make little use of them. We explore the peculiarities of the business model of banking, its impact on cash flow as well as the information needed for analysing the strategic liquidity of a bank. Based on our findings, we do not recommend investment and credit analysts to change their opinion on the usefulness of cash flow statements for banks.
urn:nbn:de:101:1-2008072200
Keywords: M41; 330; Cash flow statements for firms; cash flow statements for banks; cash flow analysis; shareholder value analysis; debtholder value analysis; credit analysis; analysis of accounting policy